Implementation intention and planning interventions in Health Psychology: Recommendations from the Synergy Expert Group for research and practice. Issue 7 (2nd July 2016) - Hagger, Martin S.; Luszczynska, Aleksandra; de Wit, John; Benyamini, Yael; Burkert, Silke; Chamberland, Pier-Eric; Chater, Angel; Dombrowski, Stephan U.; van Dongen, Anne; French, David P.; Gauchet, Aurelie; Hankonen, Nelli; et al.
Abstract : The current article details a position statement and recommendations for future research and practice on planning and implementation intentions in health contexts endorsed by the Synergy Expert Group. The group comprised world-leading researchers in health and social psychology and behavioural medicine who convened to discuss priority issues in planning interventions in health contexts and develop a set of recommendations for future research and practice. The expert group adopted a nominal groups approach and voting system to elicit and structure priority issues in planning interventions and implementation intentions research. Forty-two priority issues identified in initial discussions were further condensed to 18 key issues, including definitions of planning and implementation intentions and 17 priority research areas. Each issue was subjected to voting for consensus among group members and formed the basis of the position statement and recommendations. Specifically, the expert group endorsed statements and recommendations in the following areas: generic definition of planning and specific definition of implementation intentions, recommendations for better testing of mechanisms, guidance on testing the effects of moderators of planning interventions, recommendations on the social aspects of planning interventions, identification of the preconditions that moderate effectiveness of planning interventions and recommendations for research on how people use plans.